(untitled) (UTC Prospectivas: Journal of Administrative and Economic Sciences, 2026)
The objective of this study was to identify perceptions and determine the effectiveness of tourism marketing strategies implemented by the tour operator, using neuromarketing tools and digital metrics on social media. The applied research was mixed for heat map studies and quantitative for the analysis of Meta Business Suite and the business center of the Facebook and TikTok platforms. It was an experimental study of visual perception using eye tracking with Tobii Pro Lab software and a quantitative approach to the analysis of indicators within the Facebook and TikTok platforms. A population of 351 was used for perception, with convenience sampling of 50 subjects, and for effectiveness, a population of 225 active users was used, with sampling based on inclusion criteria. The results indicated that digital marketing and audiovisual content on TikTok managed to attract the attention of the target audience and achieve organic virality without the need for direct monetary investment. According to eye tracking, visual attention was guided by high-impact visual elements such as short phrases, large headlines, and contrasting colors. This allowed the message to be quickly prioritized, which directly impacts the perception and emotional connection of the tourist customer. In conclusion, the design and execution of tourism campaigns are improved by incorporating neuroscientific techniques and digital analysis, which enables a greater understanding of consumer visual behavior in digital environments.